Application of the Principle of Piercing the Corporate Veil in Resolving Corporate Responsibility Cases in Indonesia - Dewi, Sandra (International Journal of Law and Public Policy (IJLAPP), 2020)
This research aims to explain the application of the Principle of Piercing The Corporate Veil in resolving corporate responsibility cases in Indonesia. The method used in this research is normative legal research, using a statutory approach. The results of the research explain that based on Article 3 paragraph (1) of Law Number 40 of 2007 concerning Limited Liability Companies, it is stated that the shareholders of the company aren’t personally responsible for the agreements made on behalf of the company and aren’t responsible for the company's losses exceeding the shares they own. However, the doctrine in corporate law recognizes the existence of the Principle of Piercing the Corporate Veil which can break through the limited liability of the company's shareholders into unlimited liability up to their personal assets. Although the Principle of Piercing the Corporate Veil has been regulated in Law Number 40 of 2007 concerning Limited Liability Companies, there have been major cases in which the shareholders of the company were responsible up to their personal assets but only limited responsibility for the shares they owned. These major cases include the PT Lapindo Brantas case in 2006 and the PT Bank Century case in 2008.